Reverse transcription polymerase chain reaction (RT-PCR) based detection and serotyping of FMD Virus from field samples of Gazipur, Bangladesh, and adaptation of the virus in BHK-21 cell - Alam, Mohammad Ashraful; Rahman, Marzia; Hossen, Md. Liakot; Ahmed, Sultan; Parvej, Shafiullah; Khan, Mohammad Ferdousur Rahman; Rahman, M. Bahanur (Journal of Advanced Veterinary and Animal Research, 2015)
The study aimed for the detection and serotyping of Foot and Mouth Disease virus (FMDV) circulating in Kapasia Upazila, Gazipur district of Bangladesh during 2013. Twelve samples comprising of tongue epithelium (n=8) and inter digital tissue (n=4) were collected from suspected cattle, and inocula were prepared. The inocula were inoculated into confluent BHK-21 cell line for virus propagation. After 3 subsequent passages; progressive cytopathic effects (CPE) specific for FMDV i.e., rounding and flattening of cells, breaking down of the intercellular bridge and finally cell death (almost 100%) were observed; these were indicative of successful virus propagation in the cells. Viral RNA was extracted, and Reverse Transcription Polymerase Chain Reaction (RT-PCR) was performed using three sets of primers corresponding to the serotype O, Asia-1 and A, respectively. Out of the 12 samples, 10 (83.33%) were found to be positive for FMDV, and all of those were of serotype O. It is concluded that FMDV serotype O is circulating among the cattle of Gazipur district, Bangladesh. http://dx.doi.org/10.5455/javar.2015.b88